THE EFFECT OF USING CHAT GPT ON STUDENTS CREATIVITY LEARNING - Melinda; Sriwardona; Mawadah Rohmah, Mutia; Rati, Dasri (Mandeh : Jurnal Pendidikan Islam, 2024)
This study aims to determine the use of GPT Chat at Senior High School 1 Lembah Melintang, to assess students' learning creativity, and to determine the effect of GPT Chat on students' learning creativity at Senior High School 1 Lembah Melintang. This research is motivated by the rapid development of artificial intelligence (AI) technology in education, particularly through the use of GPT Chat as a learning tool. Although GPT Chat offers many benefits in accelerating information access and supporting students' independent learning, there are concerns that this technology may reduce students' critical and independent thinking skills. This is a quantitative study with a randomly selected sample of 50 students. Data processing was performed using SPSS 24.0 software to test validity, reliability, descriptive statistics, simple regression, and hypothesis testing. Based on the results of this study, it can be concluded that the use of GPT Chat at Senior High School 1 Lembah Melintang has a positive impact on students' learning creativity, with the majority of students experiencing improvements in material understanding and creative thinking. However, the effect of GPT Chat on student learning creativity was not statistically significant, with a low R-square value (0.023) and an insignificant t-test result. Nevertheless, this technology can still enrich students' learning experiences, as long as it is used judiciously and does not replace the important role of social interaction and teacher guidance in the learning process.